Septoplasty‐mediated improvements in nasal patency and pulmonary function: A prospective study - Francisco Alves deSousa; João Tavares Correia; João Carvalho Almeida; Sara Raquel Azevedo; Miguel Gonçalves Ferreira; Manuel Magalhães; Mariline Santos (Laryngoscope Investigative Otolaryngology, 2025)
Abstract Background and Objective Septoplasty and turbinate reduction surgery (STR) is hypothesized to affect pulmonary function by modifying airway dynamics. This study investigates the impact of STR‐mediated improvements in nasal patency on pulmonary function tests (PFTs). Methods In a prospective analysis, 37 adult patients undergoing STR were enrolled. Peak nasal inspiratory flow (PNIF) and PFT parameters, including forced expiratory flow at 25% (FEF25) and 75% of forced vital capacity (FEF75) and forced expiratory flow between 25 and 75% of the pulmonary volume (FEF25–75), forced vital capacity (FVC), and forced expiratory volume in one second (FEV1), were measured before and after surgery. Results Significant improvements were observed in PNIF (p < .001). Additionally, significant improvements in peripheral airway function occurred, as measured by FEF25, FEF25‐75, and FEF75 (p < .05), suggesting reduced airway resistance after STR. Notably, a significant positive correlation was found between the change in PNIF (∆PNIF) and the change in various PFT measurements (∆PFT) (p < .05). FVC and FEV1 did not show significant changes. Conclusions These findings suggest that improving nasal patency through STR can affect lower airway resistance, potentially benefiting patients with nasal obstruction. The observed positive correlation between ∆PNIF and ∆PFT warrants further investigation into the underlying mechanism. Level of evidence Level III.